PERTUMBUHAN DAN HASIL DUA VARIETAS TOMAT AKIBAT PERLAKUAN JENIS PUPUK - Puspita Dewi; Jumini Jumini (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2012)
Objectives of the study were to determine effects of organic fertilizer on growth and yield of two varieties of tomato as well as the interaction between both factors. Factors studied were 1) types of organic fertilizer, consisted of 3 levels: manure, compost and green manure and 2) varieties of tomatoes, consisted of two levels: Viccario F1 and San Marino F1. Variables observed were plant height and stem diameter at ages 15, 30 and 45 days after transplanting (DAT), fruit numbers, and fruit weight for 5 times of harvest. The results showed that types of organic fertilizer exerted significant effects on plant height at age of 15 and 30 DAT, plant stem diameter at age 15 and 30 DAT, fruit numbers and fruit weight. The best growth of tomato was on green manure. Varieties also exerted significant effects on plant height at ages 15, 30 and 45 DAT, stem diameter at ages 30 and 45 DAT, fruit numbers and fruit weight, but no significant effect on stem diameter at age 15 DAT. The best growth and fruit numbers wer found at Viccario, while the highest fruit weight was found at variety San Marino. There was a significant interaction between types of organic fertilizer and tomato varieties on plant height at age 45 DAT, but no significant interaction on other variables. The best plant growth was found at the combination of Viccario-manure.